2002
DOI: 10.1103/physrevd.66.104028
|View full text |Cite
|
Sign up to set email alerts
|

Black hole solutions in braneworlds with induced gravity

Abstract: We extent our previous study on spherically symmetric braneworld solutions with induced gravity, including non-local bulk effects. We find the most general static four-dimensional black hole solutions with g tt = −g −1 rr . They satisfy a closed system of equations on the brane and represent the strong-gravity corrections to the Schwarzschild-(A)dS 4 spacetime. These new solutions have extra terms which give extra attraction relative to the Newtonian-(A)dS 4 force; however, the conventional limits are easily o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 49 publications
1
65
0
1
Order By: Relevance
“…In this spirit, black hole and wormhole solutions [6,9,16,17] as well as star solutions on the brane [18] have been obtained in the last years. We should mention that even without relaxing this condition, previous solutions have also been found [19,20]. In this context the hamiltonian constraint can be written explicitly in terms of A and B as [6,9] B A ′′ A − 1 2…”
Section: Brane Black Hole Solutionsmentioning
confidence: 99%
“…In this spirit, black hole and wormhole solutions [6,9,16,17] as well as star solutions on the brane [18] have been obtained in the last years. We should mention that even without relaxing this condition, previous solutions have also been found [19,20]. In this context the hamiltonian constraint can be written explicitly in terms of A and B as [6,9] B A ′′ A − 1 2…”
Section: Brane Black Hole Solutionsmentioning
confidence: 99%
“…In addition, it suffers from a Gregory-Laflamme instability [60,61]. Despite the numerous attempts to derive a regular, asymptotically AdS blackhole solution localised on a brane with a non-vanishing tension (for an indicative list of papers, see [62,63,64,65,66,67,68,69,70,71,72]; for a more complete list of references, see [30,31,32]), up to today no analytical solution has been constructed. Numerical studies [73,74,75] found black-hole solutions with horizon radius smaller than or of the order of the AdS length ℓ AdS in the context of five-and six-dimensional warped models.…”
Section: Black Holes In Rs Brane-worldsmentioning
confidence: 99%
“…Note that the solutions (21)- (25) are the generic braneworld solutions and have been obtained without any assumption for the bulk space. It is now obvious that the only possible static exterior solution (15), surrounding the collapsing region, cannot take one of the permissible forms (21), (22), (24) of induced-gravity theory, which means that the no-go theorem for induced gravity has been proved.…”
mentioning
confidence: 99%
“…For spherically symmetric braneworld metrics of the form (12), the system of Eqs. (16)- (20) was fully integrated in vacuum in [14], [15], and the results are as follows. For E µ ν = 0 on the brane, the solution is Schwarzschild-(A)dS 4…”
mentioning
confidence: 99%